DINAMIKA MASA JABATAN HAKIM KONSTITUSI DI INDONESIA - Syah Ramadhan Putra, (Fakultas Hukum Universitas Islam Kadiri (UNISKA) Kediri, 2024)
This research examines the dynamics of the terms of office of Constitutional Justices in Indonesia. The aim of this research is to analyze the development of the term of office of Constitutional Judges in Indonesia and to analyze the terms of office of Constitutional Justices in several other countries.. The type of research used is normative legal research. The research results reveal that there is an abnormality in the implementation of the Third Amendment to the Constitutional Court Law. When the Third Amendment to the Constitutional Court Law comes into force, constitutional judges who are currently serving are deemed to have fulfilled the requirements. When there is a change in the term of office of a Constitutional Judge in the middle of the road, transitional law applies. Changing the law without implementing transitional law can be considered a violation of the constitution. This is because the constitution is the basic law that regulates the constitutional system and the life of the nation and state. Changing the law without implementing transitional law can create legal uncertainty. Therefore, legal changes must be carried out taking into account constitutional principles and enacting appropriate transitional laws. The author suggests that it is necessary to revise the Constitutional Court Law to establish clear transitional provisions for changing the term of office of Constitutional Judges and that the regulation of the term of office of Constitutional Justices can be improved by adopting the model for the term of office of Constitutional Justices in Austria, which allows for stability and rejuvenation and prevents excessive accumulation of power.